Effect of pH on morphology and supercapacitive properties of manganese oxide/polypyrrole nanocomposite - Gan, J.K.; Lim, Y.S.; Huang, N.M.; Lim, H.N. (Elsevier, 2015)
In the present work, manganese oxide/polypyrrole (MnO2/PPy) nanocomposites with compact sheet, fibrous-porous, and granular morphologies were successfully synthesized using a simple, one step in situ chemical synthesis method. Their morphologies were tunable by varying the pH of the reactant's solution, which was very simple and scalable. Moreover, their electrochemical behaviors were greatly influenced by the pH of the reactant's solution. The optimum pH condition was found to be 4.0, producing an MnO2/PPy nanocomposite with high porosity. The porosity of the nanocomposite effectively improved its specific surface area, and its pore accessibility enabled the rapid intercalation/deintercalation of the electrolyte. As a result, a high specific capacitance of up to 312 F g(-1) at 10 mV s(-1) was obtained for the porous nanocomposite. A symmetric supercapacitor device built from the porous MnO2/PPy nanocomposite yielded a specific capacitance of 142 F g(-1) per mass of one electrode and exhibited remarkable cycling stability, with 93.2% capacitance retention over 1000 charge/discharge cycles. These features show the promise of porous MnO2/PPy nanocomposite as an electrode material for high-performance supercapacitors. (C) 2015 Elsevier B.V. All rights reserved.